Creating the 5th Edition of Lees’ Loss Prevention in the Process Industries – What is Lees 5, Why is it Important, and How to Overcome Editorial Challenges? - Hans Pasman; Piet Knijff (Chemical Engineering Transactions)
First created in 1980 by Prof. Frank P. Lees of Loughborough University, and later elaborated further by Prof Sam Mannan of Texas A&M University, the four successive editions of “Lees’ Loss Prevention in the Process Industries” have been recognized as The Process Safety Reference book, especially in the academic world. Especially in recent years, Process Safety practitioners in the process industries however consulted Lees’ to a much lesser extent, as they found the scientific approach rather distinct from their daily challenges. Also, the international perspective was found underdeveloped. Currently, we are experiencing a rapid technology transition (digitalization, decarbonisation, electrification). New developments in risk analysis can no longer mature in academia for years, they need to be applied in industrial practice much sooner than was the case in previous decades. Prof. Faisal Khan of Texas A&M University concluded, therefore, that there is a need for a sound, international, state-of-the-art overview of Loss Prevention, connecting ‘daily’ industry applied practices and advanced academic knowledge, to serve as a reference for anyone active in this field. Just an update of the previous edition of Lees would not do, a completely new set-up was needed. This ambition presents numerous challenges:How to appeal to both academia and industry?How to be relevant as a reference book and process safety handbook in this age of internet access to all kinds of (unfiltered) information?How to be comprehensive, i.e., address well-established methods as well as recently developed ones?How to interlink foundations and concepts, distributed over many process safety books and papers. How to ensure the international applicability of the methods described?How to appeal to both seniors as well as starters?And last but not least: How to find contributors who have the drive, expertise, and time to voluntarily reshape the legacies of Frank Lees and Sam Mannan?Efforts to try and reconcile all the above aspects in the Lees’5th Ed. project will be described by Hans Pasman (academic perspective) and Piet Knijff (industrial perspective). The presenters may reach out to the audience as well: numerous contributors participate in the project already, but additional expertise is likely still to be required in order to complete this ambitious project. Therefore, if safety is your second nature and you have the drive, expertise, and time to help reshape this Process Safety Handbook, do not miss out on this presentation.